Giant Isolated Hydatid Cyst of Spleen - Mehdi, Soufi; Ghizlane, Kharrasse; Khanoussi, wafae; Zahi, Ismaili; Tijani, El haroudi; Mohammed, Bouziane (Journal of Spleen And Liver Research, 2015)
Liver is most commonly involved organ in hydatid cyst. Primary splenic hydatid cysts are rare; we report a case of an isolated giant hydatid cyst of spleen in a 17-year-old man. The diagnosis was confirmed by imaging findings and serology. Partial cystectomy was performed with success. In cystic lesions of spleen, hydatid cyst should be kept in patrician’s mind in the differential diagnosis. Although splenectomy is the gold standard for treating hydatid disease of the spleen, in young patient spleen-preserving surgery seems give good results.
Keywords: spleen-preserving surgery; splenectomy; hydatid cyst; spleen